2021
DOI: 10.14232/ejqtde.2021.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Special cases of critical linear difference equations

Abstract: In this paper, we investigate even-order linear difference equations and their criticality. However, we restrict our attention only to several special cases of the general Sturm–Liouville equation. We wish to investigate on such cases a possible converse of a known theorem. This theorem holds for second-order equations as an equivalence; however, only one implication is known for even-order equations. First, we show the converse in a sense for one term equations. Later, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Quite recently in [28] we have shown that the claim in Theorem 1 is not correct by presenting a counterexample in the class of difference equations with interlacing indices. The class of equations seems quite suitable for providing some counterexamples in the theory of difference equations (see, e.g., recent paper [4]).…”
Section: A Previous Claimmentioning
confidence: 99%
See 1 more Smart Citation
“…Quite recently in [28] we have shown that the claim in Theorem 1 is not correct by presenting a counterexample in the class of difference equations with interlacing indices. The class of equations seems quite suitable for providing some counterexamples in the theory of difference equations (see, e.g., recent paper [4]).…”
Section: A Previous Claimmentioning
confidence: 99%
“…Box 11099, Taif 21944, Saudi Arabia. 4 Faculty of Electrical Engineering, University of Belgrade, Bulevar Kralja Aleksandra 73, 11000 Beograd, Serbia. 5 Faculty of Mechanical and Civil Engineering in Kraljevo, University of Kragujevac, 36000 Kraljevo, Serbia.…”
Section: Fundingmentioning
confidence: 99%
“…The equations are then classified on the basis of their criticality. The high topicality of the investigated issue is evidenced by a number of recent articles on this topic [8,15,17,27], but the issue under investigation is also related to the rapidly developing theory of the critical constant [18][19][20][21][22] (in other time domains, see [23,24,50,52] and the references cited therein).…”
Section: Introductionmentioning
confidence: 99%
“…Among other important features, difference equations are related to the discretization of differential equations [6,27,29] (see also [32]). Nevertheless, the discrete calculus allows us to solve various problems directly [2, 29, chapter 1].…”
Section: Introductionmentioning
confidence: 99%
“…See, for example, the concept of conditional oscillation and the oscillation constant in Hasil and Veselý. 8 We also refer the reader to see related articles, [9][10][11][12][13][14][15] and also in the continuous and time-scale domain, we recommend related references. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Furthermore, oscillation and other properties of perturbed equations are investigated in previous studies [31][32][33][34][35][36] as well.…”
Section: Introductionmentioning
confidence: 99%